Find Tuition/Enrichment Centres

AskQ logo

STUCK ON HOMEWORK?

ASK FOR HELP FROM OUR KIASUPARENTS.COM COMMUNITY!

Question

Answer

Since p2 is inversely proportional to 2q – 1,
p2 = k / (2q – 1)

When q = 0.6,
p2 = k / [2(0.6 – 1]
p2 = k / (1.2 – 1)
p2 = k / 0.2
p2 = 5k

When q = 8/15,
p2 = k / [2(8/15) – 1]
p2 = k / (1/15)
p2 = 15k

Since sum in values of p2 when q = 0.6 and q = 8/15 is 60,
15k + 5k = 60
20k = 60
k = 3

General formula is therefore:
p2 = 3 / (2q – 1)

when q = 6.5,
p2 = 3 / [2(6.5) – 1]
p2 = 3 / 12
p2 = 1 / 4
p = ± (1/4)

p = 1/2 or p = -1/2

0 Replies 1 Like ✔Accepted Answer
Find Tuition/Enrichment Centres